Karaoke Culture - Sara Noor (Slovo, 2012)
Karaoke Culture. By DUBRAVKA UGREŠIĆ. Translated by DAVID WILLIAMS. Pp. 324. Rochester, NY: Open Letter. 2011. $15.95. Paperback. ISBN: 9781934824573. Click here to read the full review.